Geotechnical Aspects of Underground Construction in Soft Ground (Taylor & Francis, 2024)
GEOTECHNICAL ASPECTS OF UNDERGROUND CONSTRUCTION IN SOFT GROUND comprises a collection of 68 contributions, including 55 technical papers, 6 General Reports, 5 Keynotes, 1 Fujita Lecture, and 1 Bright Spark Lecture presented at the 11th International Symposium on Geotechnical Aspects of Underground Construction in Soft Ground (IS-Macau 2024), held in Macao SAR, China, on June 14-17, 2024.